Teacher Educator, Go Measure Thyself: Self-Reflection and Judgement of the Teachers of Teachers - Christopher Spencer (European Teacher Education Network, 2016)
In offering a reflection on my original 2008 study, "Teacher educator, go educate thyself: who teaches the teachers of teachers? Establishing a Model of Professional Formation for Teacher Educators in Further Education Colleges, I offer a reflection on dialogue held with educators of teachers in the UK, Canada, Holland, Australia and the USA. This process has led to insights into how they view the existence of Standards for Teacher Educators (or their absence) in relation to identifying appropriate opportunities for continuing personal and professional development. In particular, this reflective study considers how to maintain and continue to develop professional skills and knowledge.